Conformational control in the SuperQuat chiral auxiliary 5,5-dimethyl-4-iso-propyloxazolidin-2-one induces the iso-propyl group to mimic a tert-butyl group - Bull, S; Davies, S; Key, MS; Nicholson, R; Savory, E (2000)
1H NMR nOe spectroscopic studies reveal that conformational control in the enolates of N-acyl-5,5-dimethyl-4-iso-propyloxazolidin-2-ones ensures that the stereodirecting effect of its 4-iso-propyl-5,5-dimethyl functional group affords superior levels of facial selectivity normally associated with enolates derived from N-acyl-4-tert-butylox-azolidin-2-ones.